Corporate citizenship successful strategies for responsible companies - McIntosh, Malcolm 1953-; Leipziger, Deborah; Jones, Keith; Coleman, Gill (Financial Times / Pitman Publishing, 1998)
International companies such as Levis, Toys-R-Us, Avon, Nike, McDonalds, Texaco, Reebok, Sony and the White House Task Force have learned that putting corporate citizenship at the heart of corporate strategy has given them the competitive edge. The book profiles their efforts and provides innovative and visionary solutions to issues including Human Rights, Fair Trade, Social and Ethical Auditing, Environmental Policy, Stakeholder Relations, Global Codes of Conduct and Corporate Governance. These issues carry such weight in the business world that many international corporations, Avon in particular, are requiring that all suppliers be SA8000 certified, or lose their business.